ESMO expert consensus statements on cancer survivorship: promoting high-quality survivorship care and research in Europe - Vaz-Luis, Ines; Masiero, M.; Cavaletti, G.; Cervantes, A.; Chlebowski, R. T.; Curigliano, G.; Felip, E.; Ferreira, A. R.; Ganz, P. A.; Hegarty, J.; Jeon, J.; Johansen, C.; et al. (Annals of oncology, 2022)
Background - The increased number of cancer survivors and the recognition of physical and psychosocial challenges, present from cancer diagnosis through active treatment and beyond, led to the discipline of cancer survivorship. - Design and methods - Herein, we reflected on the different components of survivorship care, existing models and priorities, in order to facilitate the promotion of high-quality European survivorship care and research. - Results - We identified five main components of survivorship care: (i) physical effects of cancer and chronic medical conditions; (ii) psychological effects of cancer; (iii) social, work and financial effects of cancer; (iv) surveillance for recurrences and second cancers; and (v) cancer prevention and overall health and well-being promotion. Survivorship care can be delivered by structured care models including but not limited to shared models integrating primary care and oncology services. The choice of the care model to be implemented has to be adapted to local realities. High-quality care should be expedited by the generation of: (i) focused and shared European recommendations, (ii) creation of tools to facilitate implementation of coordinated care and (iii) survivorship educational programs for health care teams and patients. The research agenda should be defined with the participation of health care providers, researchers, policy makers, patients and caregivers. The following patient-centered survivorship research areas were highlighted: (i) generation of a big data platform to collect long-term real-world data in survivors and healthy controls to (a) understand the resources, needs and preferences of patients with cancer, and (b) understand biological determinants of survivorship issues, and (ii) develop innovative effective interventions focused on the main components of survivorship care. - Conclusions - The European Society for Medical Oncology (ESMO) can actively contribute in the efforts of the oncology community toward (a) promoting the development of high-quality survivorship care programs, (b) providing educational material and (c) aiding groundbreaking research by reflecting on priorities and by supporting research networking.